The effect of the 2009 revised U.S. guidelines for gestational weight gain on maternal and infant health: a quasi-experimental study - Daniel F. Collin; Richard Pulvera; Rita Hamad (BMC, 2023)
Abstract Background Excess gestational weight gain (GWG) has adverse short- and long-term effects on the health of mothers and infants. In 2009, the US Institute of Medicine revised its guidelines for GWG and reduced the recommended GWG for women who are obese. There is limited evidence on whether these revised guidelines affected GWG and downstream maternal and infant outcomes. Methods We used data from the 2004-2019 waves of the Pregnancy Risk Assessment Monitoring System, a serial cross-sectional national dataset including over 20 states. We conducted a quasi-experimental difference-in-differences analysis to assess pre/post changes in maternal and infant outcomes among women who were obese, while "differencing out" the pre/post changes among a control group of women who were overweight. Maternal outcomes included GWG and gestational diabetes; infant outcomes included preterm birth (PTB), low birthweight (LBW), and very low birthweight (VLBW). Analysis began in March 2021. Results There was no association between the revised guidelines and GWG or gestational diabetes. The revised guidelines were associated with reduced PTB (− 1.19% points, 95%CI: − 1.86, − 0.52), LBW (− 1.38% points 95%CI: − 2.07, − 0.70), and VLBW (− 1.30% points, 95%CI: − 1.68, − 0.92). Results were robust to several sensitivity analyses. Conclusion The revised 2009 GWG guidelines were not associated with changes in GWG or gestational diabetes but were associated with improvements in infant birth outcomes. These findings will help inform further programs and policies aimed at improving maternal and infant health by addressing weight gain in pregnancy.